Pelatihan Dan Pemdampingan Mahasiswa Dalam Penyusunan Tugas Akhir dengan Tools Artificial Intelligence - Muhammad Akbar; Rita Yunus; Vera Sri Endah Cicilia; Rangga Putera Boroallo (JPM: Jurnal Pengabdian Masyarakat, 2025)
This activity aims to carry out training and assistance for students in preparing final assignments by utilising AI web-based tools. The tools used include Open Knowledge Maps, Publish or Perish for reference search, DeepL for translation, Mendeley for reference management, QuillBot for paraphrasing, and Turnitin for plagiarism checking. The programme consisted of face-to-face workshops and mentoring sessions, both offline and online, which included demonstrations, practical exercises, and assistance in applying the tools for the final project. The results of this activity showed a significant improvement in the quality and efficiency of the final assignments of students who participated in this activity with an average increase of 13.54 per cent, because AI tools make it easier to find references, translate, write, reference management, paraphrase, and check plagiarism. This makes students more efficient and reduces stress. Therefore, the use of AI tools proved to be effective in overcoming the challenges in preparing the final project, and this training programme is highly recommended for higher education institutions.